Severe obesity and fitness in New York City public school youth, 2010-2018 - Cody D. Neshteruk; Sophia E. Day; Kevin J. Konty; Sarah C. Armstrong; Asheley C. Skinner; Emily M. D'Agostino (BMC, 2023)
Abstract Background Obesity is associated with poorer youth fitness. However, little research has examined the magnitude of this relationship in youth with severe obesity. Therefore, we sought to determine the relationship between increasing weight status and fitness within a sample of children and adolescents from New York City public schools. Methods This study utilized longitudinal data from the NYC Fitnessgram dataset years 2010-2018. Height and weight along with fitness were measured annually during physical education classes. Severity of obesity was defined using body mass index relative to the 95th percentile and then categorized into classes. A composite measure of fitness was calculated based on scores for three fitness tests: aerobic capacity, muscular strength, and muscular endurance. To examine the weight status-fitness relationship, repeated measures mixed models with random-intercepts were constructed. Stratified models examined differences by demographic factors. Results The sample included 917,554 youth (51.8% male, 39.3% Hispanic, 29.9% non-Hispanic Black, 14.0%, 4.6%, and 1.6% class I, II and III obesity, respectively). Compared to youth with healthy weight, increasing severity of obesity was associated with decreased fitness: overweight (β = − 0.28, 95% CI:-0.29;-0.28), class I obesity (β = − 0.60, 95% CI:-0.60; − 0.60), class II obesity (β = − 0.94, 95% CI:-0.94; − 0.93), and class III obesity (β = − 1.28; 95% CI:-1.28; − 1.27). Stratified models showed the association was stronger among male and non-Hispanic White youth. Conclusion Findings revealed that more severe obesity was associated with lower fitness. Future research is needed to develop targeted interventions to improve fitness in youth with obesity.